Infection with human immunodeficiency virus-1 increases expression of vascular endothelial cell growth factor in T cells: implications for acquired immunodeficiency syndrome-associated vasculopathy. - Ascherl, Gudrun; Hohenadl, Christine; Schatz, Octavian; Shumay, Elena; Bogner, J.; Tschachler, Erwin; Monini, Paolo; Ensoli, Barbara; Stürzl, Michael; et al. (Blood, 1999)
Alterations in the vascular system and the onset of angioproliferative lesions such as Kaposi's sarcoma (KS) are common traits of human immunodeficiency virus-1 (HIV-1)-infected patients. To investigate possible factors involved in acquired immunodeficiency syndrome (AIDS)-associated vasculopathy and vascular malfunction, expression of vascular endothelial cell growth factor-A (VEGF-A) was analyzed in HUT 78 T lymphocytes upon infection with HIV-1. VEGF-A was found to be increased in supernatants from infected cells as compared with uninfected cells. In addition, VEGF-A mRNA expression and protein secretion were significantly increased in HUT 78 cells incubated with conditioned medium (CM) derived from HIV-1 chronically infected HUT 78 cells (HIV-TCM) as compared with CM from uninfected cells (TCM). Increase of VEGF-A production in T cells was promoted by inflammatory cytokines (IC) present in HIV-TCM, including tumor necrosis factor alpha (TNFalpha), interferon gamma (IFNgamma), interleukin-1beta (IL-1beta), and IL-6. These IC that have been shown to be increased in sera of HIV-1-infected patients and to be increased by HIV-1 infection or cell activation in these individuals as well as HIV-TCM also increased VEGF-A expression in primary T lymphocytes. Consistent with this, VEGF-A concentrations were found to be higher in sera of HIV-1-infected patients with (mean, 357.1 +/- 197.9 pg/mL) and without KS (mean, 256.7 +/- 137.5 pg/mL) as compared with uninfected individuals (mean, 188.6 +/- 91.7 pg/mL). These data suggest that increased secretion of VEGF-A by T lymphocytes of HIV-1-infected individuals may induce vascular leakage and stimulate proliferation of vascular endothelial cells, which are hallmarks of AIDS-associated vasculopathy and especially of KS development.